Evaluasi Pelaksanaan Penguatan Permodalan Koperasi di Kota Payakumbuh - Purnama Sari, Ulan Indah (Dinasti Review Publisher, 2023)
Abstract: This article was written to describe the utilization of cooperative capital strengthening which consists of utilizing and returning funds for strengthening capital in the City of Payakumbuh. This type of research used is evaluative. Sampling was taken by purposive sampling technique. The findings of the study are: 1) in the process of utilizing capital strengthening funds there are still lending cooperatives that do not use their loans in accordance with predetermined conditions, namely there are still warehouses where the loans are used by other people, and 2) in the implementation of repaying loans to capital strengthening funds there are still many cooperatives loans that do not repay loans in accordance with the stipulated time, of the 26 loan cooperatives recorded in 2013 there were 69.1% of cooperatives that failed to repay loans or around 18 cooperatives. Abstrak: Artikel ini ditulis untuk mendeskripsikan tentang pelaksanaan penguatan permodalan koperasi yang terdiri dari pelaksanaan pemanfaatan dan pengembalian dana penguatan permodalan di Kota Payakumbuh. Jenis penelitian yang digunakan adalah evaluatif. Penentuan sampel diambil dengan teknik Purposive Sampling. Temuan penelitian yaitu: 1) pada proses pemanfaatan dana penguatan permodalan masih terdapat koperasi peminjam yang tidak memanfaatkan pinjamannya sesuai dengan ketentuan yang telah ditetapkan yaitu masih terdapat peminjam dimana pinjamannya dimanfaatkan oleh orang lain, dan 2) pada pelaksanaan pengembalian pinjaman dana penguatan permodalan masih banyak koperasi peminjam yang tidak mengembalikan pinjamannya sesuai dengan waktu yang telah ditetapkan, dari 26 koperasi peminjam yang tercatat pada tahun 2013 terdapat 69,1% koperasi yang macet dalam mengembalikan pinjaman atau sekitar 18 koperasi.